2017
DOI: 10.1111/ggi.13083
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy is safe and effective in achalasia patients aged older than 60 years compared with younger patients

Abstract: As well as in younger patients, POEM can be safely carried out in elderly patients, providing significant symptom relief. POEM might be recommended as the first therapeutic approach to elderly achalasia patients. Geriatr Gerontol Int 2017; 17: 2407-2413.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…748 records were screened, and 88 full-length articles were assessed. Sixty-six studies 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 were included in the final analysis, four of which directly compared outcomes of POEM to PD 32 35 36 38 . A total of 29 studies reported on the outcomes of POEM 24 …”
Section: Resultsmentioning
confidence: 99%
“…748 records were screened, and 88 full-length articles were assessed. Sixty-six studies 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 were included in the final analysis, four of which directly compared outcomes of POEM to PD 32 35 36 38 . A total of 29 studies reported on the outcomes of POEM 24 …”
Section: Resultsmentioning
confidence: 99%
“…Peroral endoscopic myotomy for EMD is minimally invasive and has a high success rate in elderly patients 7 . Thus, clinical practice guidelines for POEM from JGES 15 state that POEM is a safe and effective procedure for elderly patients as an answer to the clinical question regarding the effectiveness of POEM in treating elderly patients with esophageal achalasia.…”
Section: Discussionmentioning
confidence: 99%
“…Peroral endoscopic myotomy is considered as one of the useful therapeutic options for the elderly with EMD because of its minimal invasiveness and effectiveness. The comparison of the safety and efficacy of POEM for EMD in adults aged 60 years and above and adults under 60 years has already been reported 7 . Studies on EMD in adults aged 80 years and above have been limited to descriptive data collected in an international multicenter study about the safety and efficacy of POEM 8 .…”
Section: Introductionmentioning
confidence: 99%
“…retrospectively analyzed their data regarding the efficacy of POEM in 18 patients older than 60 years and in 95 patients younger than 60 years, they found that efficacy was 92.9% and 89.9% (success defined as an ES of ≤3), respectively, with no statistically significant differences between them. There was also no statistically significant difference in the rate of adverse events in both groups . Wang et al .…”
Section: Clinical Questions and Statementsmentioning
confidence: 99%